2014
DOI: 10.1002/pd.4322
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in gene expression in human brain during late first trimester and early second trimester of pregnancy

Abstract: For the first time, brain global gene expression was described in human samples. Period B1 was dominated by genes coding for neuronal migration, differentiation, programmed cell death and sensory organs. B3 was dominated by neuronal proliferation, branching and myelination. Creating such a database will allow comparison with abnormals in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(20 reference statements)
0
4
0
Order By: Relevance
“… 10 Primarily (though not exclusively) first-trimester fever episodes have been linked to severe brain damage and structural anomalies. 9 , 11 Although first-trimester exposure may also influence subsequent more subtle disruptions of brain development, some investigators have hypothesized that exposure to fever later in pregnancy should be more strongly related to more subtle disruptions—including effects on neuronal migration, 12 proliferation 12 , 13 and myelination 14 —such as those reported in some studies of ASD. 15 , 16 , 17 , 18 , 19 Few studies have examined the association of prenatal fever, per se , with autism outcomes, as opposed to effects of specific types of maternal infection (for example, influenza).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Primarily (though not exclusively) first-trimester fever episodes have been linked to severe brain damage and structural anomalies. 9 , 11 Although first-trimester exposure may also influence subsequent more subtle disruptions of brain development, some investigators have hypothesized that exposure to fever later in pregnancy should be more strongly related to more subtle disruptions—including effects on neuronal migration, 12 proliferation 12 , 13 and myelination 14 —such as those reported in some studies of ASD. 15 , 16 , 17 , 18 , 19 Few studies have examined the association of prenatal fever, per se , with autism outcomes, as opposed to effects of specific types of maternal infection (for example, influenza).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative gene expression analyses were performed with inventoried Taqman Gene Expression Assays (Applied Biosystems, Carlsbad, CA, USA) for the reference gene glyceraldehyde 3 - phosphate dehydrogenase (GAPDH) , and three genes associated with neurodevelopment: (1) neurexin 3(NRXN3), a neuronal cell surface protein-encoding gene involved in cell recognition and adhesion; (2) neurotrophic tyrosine kinase receptor type 3 (NTRK3), cell-surface receptor involved in neurotrophin signaling of cell differentiation; (3) and zinc finger and BTB domain containing 18 ( ZBTB18, alias ZNF238), a transcriptional repressor of genes involved in neurodevelopment. These genes were selected on the basis of prior detection in microarray studies of AF [ 2 , 6 ], documented tissue expression in human fetal brain [ 7 ] and fetal brain specific expression (defined as expression >10 multiples of the median in a publicly-available gene expression atlas [ 8 ]). The qPCR reactions were performed in duplicate on the CFX 384 (BioRad, Foster City, CA, USA), with the following cycling conditions: 50 °C for 2 min, 95 °C for 10 min, and 40 cycles of 95 °C for 15 s, and 60 °C for 1 min.…”
Section: Resultsmentioning
confidence: 99%
“…The fetal period, particularly during the first 10-18 weeks of pregnancy, is the most active period of neuron proliferation. Providing a fetus is exposed to unfavorable conditions during this window of development, neuronal proliferation and axonal extension will be directly affected (5). This may lead to decreases in the number and volume of fetal brain cells, and severe effects on interneuronal connections (5).…”
Section: Introductionmentioning
confidence: 99%
“…Providing a fetus is exposed to unfavorable conditions during this window of development, neuronal proliferation and axonal extension will be directly affected (5). This may lead to decreases in the number and volume of fetal brain cells, and severe effects on interneuronal connections (5). Samuelsen et al (6) used an optical fractionator to analyze cells in various developmental regions of the brain affected by FGR and reported that the growth rate of brain cells in the cerebral cortex peripheral region of the FGR group was significantly lower than that of the control group, and the total number of cerebral cortical cells was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%